Pengaruh Likuiditas, Profitabilitas, Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Di Sektor Perbankan - Keri Boru Hotang (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2021)
The research test the influence of liquidity, profitability, and capital structure on the value of banking firms. The type of research used is quantitative research that uses company secondary data, namely annual reports obtained from the websites of banking sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This study uses multiple linear regression test on 75 samples. The results of this indicate that liquidity (CR), profitability (ROA) and capital structure (DER) simultaneously have significant influence on firm value (PBV).